Bmi and gender as mediators in the association between ethnicity and glycemic control in primary healthcare settings: Malaysia national diabetes registry cohort / Eliana Ahmad - Eliana, Ahmad (2019)
Background: The prevalence of type 2 diabetes continues to escalate across all ethnic groups in Malaysia. Evidence on ethnic differences among Asian population mostly focused on the incidence and prevalence of diabetes, rather than on glycaemic control. Poor glycemic control leads to development of diabetes-related complications. The association between ethnicity and glycemic control was investigated. The roles of sex and body mass index (BMI) as mediators were assessed. We also determined the association between ethnicity and diabetes-related complications. Methods: A retrospective cohort study involving 338,349 primary care patients registered in the Malaysian National Diabetes Registry (NDR) between 2011 and 2015 was conducted. All major ethnic groups were included (Malays, Chinese, Indian, Indigenous Sabah [consisted of Kadazan, Dusun, Bajau and Other Sabah] and Indigenous Sarawak [consisted of Iban, Bidayuh, Melanau and Other Sarawak]). Linear mixed effect model with random intercept and logistic random intercept models were used to analyze crosssectional associations (defined as glycemic control at five years of diabetes) and longitudinal associations (defined as glycemic control for every five years of diabetes). Generalized structural equation modeling (GSEM) was used to conduct mediation analysis, and discrete-time survival analysis was used to determine the hazard of diabetes-related complications. Results: Ethnicity was significantly associated with HbA1c level. Cross-sectionally, all ethnicities were significantly associated with lower HbA1c level compared to the Malays. In the longitudinal associations, the HbA1c levels changed by 0.1% among Chinese and Indian, 0.24% among Dusun and 0.12% among Indigenous Sarawak, compared to the Malays [Chinese and Indian: β= -0.10 (95%CI - 0.13, -0.07), Dusun: β= 0.24 (95%CI 0.07, 0.41), Indigenous Sarawak: β= 0.12 (95%CI 0.01, 0.22)]. Compared to Malays, the odds of good glycemic control increased by 20% among the Indians and 7% among the Chinese [Indian: OR 1.20 (95%CI 1.13, 1.28), iv Chinese: OR 1.07 (95%CI 1.01, 1.12)], while among the Indigenous Sabah and Indigenous Sarawak, the odds decreased by 14% and 20% [Indigenous Sabah: OR 0.86 (95%CI 0.75, 0.99), Indigenous Sarawak OR 0.80 (95%CI 0.65, 0.98)]. Sex mediated the association between Chinese, Indian and Iban ethnicities and HbA1c level [Indirect associations: Chinese (0.7%), Indian (1.1%) and Iban (0.1%)]. BMI mediated the association between Chinese, Indian, Bajau, Iban and Melanau and HbA1c level (Indirect associations ranged from 0.1% to 7.0%). Compared to Malays, Indian ethnicity was associated with significantly increased hazard of diabetic retinopathy and peripheral vascular disease (PVD) [Retinopathy: HR 1.18 (95%CI 1.13, 1.23), PVD: HR 1.11 (95%CI 1.00, 1.22)]. Chinese, Bajau, and Other Sabah had an increased hazard of diabetic retinopathy [Chinese: 23%, Bajau: 93%, Other Sabah: 115%] and a decreased hazard of diabetic nephropathy [Chinese: 5%, Bajau: 51%, Other Sabah: 32%] and PVD [Chinese: 33%, Bajau: 67%, Other Sabah: 63%]. The Ibans had significantly decreased hazard for all three diabetes-related complications [Retinopathy: HR 0.62 (95%CI 0.52, 0.75), Nephropathy: HR 0.68 (95%CI 0.58, 0.79), PVD: HR 0.58 (95%CI 0.36, 0.92)]. Conclusion: Ethnicity appears to be a significant predictor of glycemic control, and diabetes-related complications. These associations are mediated by sex, and BMI. In multi-ethnic settings like Malaysia, health programs aiming for early detection of diabetes, improvement of health literacy in diabetes for better glycemic control, prevention of diabetes-related complications, and provision of supportive care should be tailored according to ethnic groups. Future studies should examine the potential mediating role of other lifestyle factors in the control of diabetes.